2004
DOI: 10.1038/oby.2004.24
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Pathway to the Manifestations of Metabolic Syndrome

Abstract: SONNENBERG, GABRIELE E., GLENN R. KRAKOWER, AND AHMED H. KISSEBAH. A novel pathway to the manifestations of metabolic syndrome. Obes Res. 2004;12:180 -186. Pathways leading from obesity to the manifestations of metabolic syndrome involve a number of metabolic risk factors, as well as adipokines, mediators of inflammatory response, thrombogenic and thrombolytic parameters, and vascular endothelial reactivity. Increased adipose tissue mass contributes to augmented secretion of proinflammatory adipokines, particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
136
0
11

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(150 citation statements)
references
References 112 publications
3
136
0
11
Order By: Relevance
“…Pathways leading from obesity to the manifestations of MS involve a number of metabolic risk factors (Sonnenberg et al, 2004). The resistance to insulin-stimulated glucose uptake is associated with multiple metabolic abnormalities.…”
Section: Ghrelin In Metabolic Syndromementioning
confidence: 99%
“…Pathways leading from obesity to the manifestations of MS involve a number of metabolic risk factors (Sonnenberg et al, 2004). The resistance to insulin-stimulated glucose uptake is associated with multiple metabolic abnormalities.…”
Section: Ghrelin In Metabolic Syndromementioning
confidence: 99%
“…These proinflammatory agents are thought to induce oxidative stress thereby exacerbating underlying pathological processes leading to dyslipidemia, glucose intolerance, insulin resistance, and endothelial dysfunction that are common in obesity and type II diabetes mellitus (T2DM) (Sonnenberg et al, 2004). Previous cross-sectional studies found both higher (Togo et al, 2004) and lower (Richards et al, 2006) adiponectin levels in patients treated with olanzapine compared to healthy controls as well as lower levels in untreated patients compared to controls (Cohn et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Also IL-6 concentrations reflected disease status and were commonly associated with metastatic disease [53] . TNF-α activates NF-κB (by phosphorylation of its inhibitor IκB), which increases production of NO, a substrate for reactive oxygen species (ROS) formation, and stimulates other inflammatory cytokines [54] . With respect to cancer, ROS can damage DNA by several processes including DNA base modification, deletions, frame shifts, strand breaks, DNA-protein cross-links, and chromosomal rearrangements.…”
Section: Inflammatory Cytokines and Colorectal Cancermentioning
confidence: 99%